Anatomic and volumetric characterization of the cisterna chyli using CT lymphangiography and computer‐assisted design software in dogs with idiopathic chylothorax. Issue 3 (3rd March 2020) - Carvajal, Jose L.; Case, J. Brad; Vilaplana Grosso, Federico; Huynh, Elizabeth; Verpaalen, Valentine; Fox‐Alvarez, Alexander; Regier, Penny J.
Abstract: The objectives of this retrospective, observational study were to characterize the anatomical features of the cisterna chyli (CC) in a cohort of dogs diagnosed with idiopathic chylothorax that underwent CT lymphangiography (CTLa), and to evaluate the feasibility of computer‐assisted design (CAD) software to quantify volumetric measurements of the CC. Twenty‐three client‐owned dogs with idiopathic chylothorax were included. Additionally, CTLa was performed in three canine cadavers to assess the ability of CAD software to accurately acquire volumetric measurements. Injection sites, attenuation values, anatomic location, dimensions, and aortic diameter to CC ratio (Ao:CC) were recorded. Video records of video‐assisted thoracic surgery (VATS) thoracic duct ligation (TDL) were reviewed in eight out of 23 dogs to compare operative and CTLa findings. The CC was dorsal and right‐sided in 18 out of 23 dogs, located between L1 and L4 in 21 dogs, and extended as far cranially as T11 in two dogs. The median measurements for length, height, and width were 150.0, 5.5, and 13.3 mm, respectively. Median total volume was 1.82 mL. Median volumes to the right and left of the aorta were 1.46 and 0.49 mL, respectively ( P = .014). Median total CC volume to body weight ratio (CC:bw) was 0.07 mL/kg. The presence of an intrathoracic CC was observed intraoperatively in six out of eight cases that underwent VATS TDL. Findings supported the use of CTLa and CAD as feasible methods for characterizing the CC in dogs diagnosed with chylothorax. These methods may facilitate interventional planning involving the CC such as embolization.